1992
DOI: 10.1111/j.1365-4362.1992.tb03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Ashy Dermatosis and Lichen Planus Pigmentosus: A Clinicopathologic Study of 31 Cases

Abstract: The clinical and histopathologic characteristics of patients with ashy dermatosis (n=20) and lichen planus pigmentosus (n=11) were analyzed. We found significant clinical differences between both dermatoses, supporting our opinion that they are two separate conditions. Both dermatoses were histologically similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
118
5
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 14 publications
9
118
5
5
Order By: Relevance
“…İlaçlar-dan ise etambutolun nadiren likenoid ve EDP benzeri erüpsiyona neden olduğu bildirilmiştir (5). EDP'nin liken planusun bir varyantı olduğu düşünülmekle birlikte, liken planustan önce ve sonra gelişen EDP olguları bildirildiği için her iki hastalığın ilişkili ayrı antiteler olabileceği öne sürülmüştür (6,7). Şekil III: Doğum sonrası lezyonlarda kısmen gerileme Navarro Jiménez ve ark.…”
Section: Discussionunclassified
“…İlaçlar-dan ise etambutolun nadiren likenoid ve EDP benzeri erüpsiyona neden olduğu bildirilmiştir (5). EDP'nin liken planusun bir varyantı olduğu düşünülmekle birlikte, liken planustan önce ve sonra gelişen EDP olguları bildirildiği için her iki hastalığın ilişkili ayrı antiteler olabileceği öne sürülmüştür (6,7). Şekil III: Doğum sonrası lezyonlarda kısmen gerileme Navarro Jiménez ve ark.…”
Section: Discussionunclassified
“…Flexural involvement including the axilla (8.9%), inframammary folds (6.5%), and groin (3.2%) was seen less frequently. Vega et al 8 published a clinicopathologic study of 11 cases of LPP describing distributions primarily in the face (73%) and trunk (45%). The axillary and inguinal folds were only affected in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, ashy dermatosis was thought to be the same condition as LPP. However, Vega et al 8 reported clinical differences between ashy dermatosis and LPP including the presence or absence of pruritis and lesion color. Pigmented contact dermatitis is a non-eczematous variant of contact dermatitis, character- ized clinically by hyperpigmentation caused by common allergens such as fragrances, preservatives and deodorants.…”
Section: Discussionmentioning
confidence: 99%
“…El liquen plano pigmentoso 32,43,44 afecta a ambos sexos y aparece entre la primera y la séptima década de vida, aunque en la mayor serie el 87% tenía entre 15 y 46 años 44 . Se presenta en forma de máculas azuladas o grisáceas, redondas u ovaladas pequeñas, mal definidas, en ocasiones confluentes, formando lesiones mayores; sus márgenes son irregulares y se atenúan hacia la periferia; afectan habitualmente la cara, frente y regiones preauriculares -casi siempre afectadas en forma inicial-, extremidades superiores, abdomen y parte alta de la espalda (céfalo-caudal).…”
Section: Figuraunclassified
“…Entre un tercio y la mitad de los casos puede haber prurito asociado. Su curso es crónico y persistente, con remisiones y recaídas 43 .…”
Section: Figuraunclassified